Cloud hosting services and resources utilizing efficient proxy server based speculative algorithm - Mahadevan, Ravi; Anbazhagan, Neelamegam (International Journal of Engineering and Technology, 2018)
Cloud computing is an envisioned technique for service providing paradigm. Currently, many enterprises and organizations are hosting data into cloud service provider to minimize the maintenance cost, energy consumption and improve the data consistency. However, the several cloud servers facing the various hosting service policies, clients may be confused with which cloud server providers are appropriate for storing data and which hosting methodology is inexpensive. The current status quo is clients frequently put data into the single cloud and simply trust to luck. In the paper, proposes a new data hosting redundancy methodology called as Efficient Proxy Server Based Speculative (EPSBS) algorithm that provides accessibility guarantee, reducing hosting service, energy consumption and enhances Quality of Services (QoS) performance concurrently and it requires integrating two key functions. The first function is choosing numerous appropriate cloud service providers and a suitable EPSBS redundancy methodology to store data with guaranteed accessibility. The second key function is triggering a transmission process to reallocate data along with the deviations of data access prototype of clouds.Â  Based on Experimental evaluations, proposed methodology reduces 0.11 ET (Execution Time), and 0.02 EC (Energy Consumption) and improves 29% HS (Hosting Service size), 2.8 T (Throughput) compared than existing methodologies.